KARAKTERISTIK KEJADIAN FILARIASIS DI PROVINSI SUMATERA UTARA - Rahmadani Sitepu; Sinta Veronica; Nanda Novziransyah (Jurnal Penelitian Kesmasy, 2019)
This study aims to characteristics of Filariasis Patients in North Sumatra Province in 2010-2017. This research used descriptive study with case report desained. This sampling was carried out using secondary data obtained from North Sumatra province in the period 2010-2017. The sample of this study was 33 districts / cities taken using the total sampling method. The sample selection is based on secondary data obtained from North Sumatera Province. The highest proportion of Filariasis sufferers in the age category is end adult as many as 16 patients (19.8%), the highest sex is more prevalent in 52 patients (64.2%), 23 Most lymphedema in filariasis patients is in Right Lower Legs (28.4%), Based on the year began to live as many as 52 patients over 10 years (64.2%), Based on the year starting from the illness, there were 52 patients over 10 years (64.2%), and by region found as many as 16 sufferers in center tapanuli (19.8%).